Influence of temporal characteristics on the power scalability of the fiber amplifier. (28th January 2015) - Wang, Wenliang; Leng, Jinyong; Gao, Yang; Guo, Shaofeng; Jiang, Zongfu
Abstract: We have performed an experimental study of the power scaling ability of a fiber amplifier limited by the temporal stability of its seed light. Three seed sources with various temporal characteristics are demonstrated for the fiber amplifier. An accurate model of the fiber amplifier is established by considering the time dynamics of the laser. The results show that the self-pulsation can reduce the SRS threshold of the fiber amplifier and limit the power scalability of the fiber amplifier.